BAGAIMANA KOMUNIKASI ORANGTUA TERKAIT PENDIDIKAN SEKS PADA ANAK REMAJA MEREKA? - Kartikasari, Aprilia; Setiawati, Nina (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2020)
Adolescents need serious attention because they are at risk of sexual and reproductive health problems. Sex education for adolescents is currently focused on a family approach, but communication with children about sex is often considered taboo by family members, especially parents. There are still many parents who say they are unable to talk about sex education with their children, in this case researchers need to know the barriers and difficulties of parents to communicate sex education to teenagers. The aims of this research was to descript parental-adolescent communication consists of discussion of parents with adolescents about problems in school, focus on current adolescents, the level of difficulty in discussing sex with children, and the topic of discussion about sexual and reproductive education. This study used descriptive analytical methods on respondents as many as 56 people who met the research criteria. The result of this study showed parent-adolescence communication about the school problems was lack, most of parents attention focus was on the school record, most of parents says difficult to talk about sex, and most of parents were not disscuse about sensitive topic on sexuallity with their children. Communication between parents and adolescents tends to be general, such as achievement in school, manners, and friendship. Most parents find it difficult to communicate regarding sexuality issues with their teenagers